(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
As for the vocabulary of the langue populaire, linguists almost unanimously speak about the loss of its social marking and the actualization of the stylistic function: "In synchronous terms, it is extremely difficult to accurately distinguish between familiar, vernacular and argotic words and expressions… The choice of a "high" (for example, importuner), "medium" (ennuyer) or "low" (embeter) word in speech may depend not on the cultural level of the subject of speech, but on the role he plays in the communication process and the attitude dictated by the role of the addressee of speech" (Dolinin 1978: 315- 318). Russian Russian is a significant difference between the French vernacular: in Russian literary speech, vernacular units can be used only for the purpose of irony, jokes, conscious stylistic contrast, etc.